2012
DOI: 10.1111/jvh.12010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of FIB‐4 and APRI in Chinese HBV‐infected patients with persistently normal ALT and mildly elevated ALT

Abstract: SUMMARY. Significant liver disease has been reported in chronic hepatitis B patients with normal alanine aminotransferase (ALT). Liver biopsy (LB) is the current gold standard for assessing hepatic inflammation and fibrosis in patients with chronic HBV. However, associated risks have led to the development of noninvasive models. Their utility in patients with normal ALT is unknown. FIB-4 and aspartate aminotransferase (AST)-to-platelet ratio index (APRI) were calculated for patients with chronic HBV infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 32 publications
5
62
0
Order By: Relevance
“…The full texts of 110 potentially eligible reports were obtained for further assessment. Of those, 30 papers were included in the review following full-text screening (Table 1); 20 studies were related to the APRI [3], [16], [17], [33]-[49], 13 studies related to the FIB-4 [3], [7], [17], [39][46], [48], [50], and 11 studies related to the FibroTest [47][49], [51][58].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The full texts of 110 potentially eligible reports were obtained for further assessment. Of those, 30 papers were included in the review following full-text screening (Table 1); 20 studies were related to the APRI [3], [16], [17], [33]-[49], 13 studies related to the FIB-4 [3], [7], [17], [39][46], [48], [50], and 11 studies related to the FibroTest [47][49], [51][58].…”
Section: Resultsmentioning
confidence: 99%
“…10 studies used a METAVIR score, 4 studies used an Ishak score, 4 studies used a Scheuer score, 1 study used a Batts and Ludwig score, and 1 study used the Chinese Hospital System. Nineteen of these studies (N = 3,955) included HBV-infected patients without comorbid conditions [3], [16], [17], [33][48]. The one remaining study included special populations of patients such as HBV/HDV-coinfected patients (N = 253) [59].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both APRI and FIB-4 are useful for identification of those without significant fibrosis [33,34]. An APRI cutoff \0.7 has a 77 % sensitivity and 79 % negative predictive value to exclude significant liver fibrosis [35].…”
Section: Noninvasive Predicting Indices Of Liver Fibrosismentioning
confidence: 99%
“…Several researchers have investigated the validity of APRI and FIB-4 for the detection of mild liver fibrosis and cirrhosis in HCV-, HBV-or HIV-infected patients. [14][15][16][17][18][19][20][21][22] The results have been controversial for predicting HBV-related liver fibrosis. Our previous study suggested that the accuracy of these two models for predicting liver fibrosis related by HBV is different from the results of the original articles.…”
Section: Introductionmentioning
confidence: 99%